Comparison of three clinical scoring systems for Culicoides hypersensitivity in a herd of Icelandic horses. Issue 6 (22nd August 2019) - Miller, Julia E.; Mann, Sabine; Fettelschoss‐Gabriel, Antonia; Wagner, Bettina
Abstract : Background: Culicoides hypersensitivity (CH), an intensely pruritic and seasonal allergic dermatitis, is a common allergic disease affecting horses worldwide. Currently, there is no validated clinical scoring system for the quantification of clinical signs associated with CH. Objectives: To (i) determine the best cut‐off point of three scoring systems, (ii) test the accuracy of each system when compared to the clinical diagnosis of an experienced veterinarian and (iii) assess agreement between systems. Animals: Icelandic horses (n = 20); eight with CH and 12 unaffected, from a research herd receiving no treatments for allergic dermatitis. Methods and materials: Lesion scores were recorded biweekly from April until September with three clinical scoring systems (A, B and C) by a single observer initially blinded to CH status. Separate logistic regression analyses for each time point were used to determine appropriate cut‐offs for CH classification. Spearman's rho and Cohen's kappa were calculated to analyze correlation of scores and agreement of CH categorization between systems, respectively. Results: The best allergic cut‐off scores for system A, B and C were determined to be three, eight and 12, respectively. For each system median areas under the curve (>0.85) were excellent and discriminatory ability for correctly classifying CH status was strong. Excellent correlation between scores for each system (Spearman's rho > 0.96) and excellent intersystem agreement for CH categorization (kappa ≥ 0.73) were found across scoring time points. Conclusion and clinical importance: Results support the use of these scoring systems as templates for the future standardization of a CH clinical scoring system. Abstract : Background– Culicoides hypersensitivity (CH), an intensely pruritic and seasonal allergic dermatitis, is a common allergic disease affecting horses worldwide. Currently there is no validated clinical scoring system for the quantification of clinical signs associated with CH.Objectives– To (i) determine the best cut‐off point of three scoring systems, (ii) test the accuracy of each system when compared to the clinical diagnosis of an experienced veterinarian and (iii) assess agreement between systems.Conclusion and clinical importance– Results support the use of these scoring systems as templates for the future standardization of a CH clinical scoring system. Résumé: Contexte: L'hypersensibilité aux piqures de culicoïdes (CH), dermatite allergiques saisonnière intensément prurigineuse, est une maladie allergique fréquente touchant les chevaux dans le monde entier. Aucun système de notation n'est à ce jour validé pour la quantification des signes cliniques associés à CH. Objectifs: Déterminer (i) le meilleur seuil de trois systèmes de notation, (ii) évaluer la précision de chaque système comparé au diagnostic clinique d'un vétérinaire expérimenté et (iii) déterminer la concordance entre les systèmes. Sujets: Des chevaux islandais (n = 20); huit avec CH et 12 sains, issus d'un troupeau de recherche ne recevant aucun traitement pour dermatite allergique. Matériels et méthodes: Les scores lésionnels ont été enregistrés deux fois par semaine d'avril à septembre avec trois systèmes de notation (A, B et C) par un seul investigateur initialement aveugle au statut CH. Les analyses de régression logistique pour chaque point ont été utilisées pour déterminer le statut approprié pour classifier en CH. Le rho de Spearman et le kappa de Cohen ont été calculés pour analyser respectivement la corrélation entre les scores et la concordance de la catégorisation de CH entre les systèmes. Résultats: Le meilleur des scores seuils des systèmes A, B et C étaient respectivement trois, huit et 12. Pour chaque système, les aires médianes sous la courbe (>0.85) étaient excellentes et la capacité de discrimination pour une classification correcte du statut CH était forte. Une corrélation excellente entre les scores pour chaque système (rho de Spearman > 0.96) et un accord inter système excellent pour la catégorisation de CH (kappa ≥ 0.73) ont été trouvés parmi la notation de chaque temps de mesure. Conclusions et importance clinique: Les résultats soutiennent l'utilisation de ces systèmes de notation comme modèle pour de futures standardisations de système de notation cliniques de CH. Resumen: Introducción: la hipersensibilidad a los culicoides (CH), una dermatitis alérgica intensamente pruriginosa y estacional, es una enfermedad alérgica común que afecta a los caballos en todo el mundo. Actualmente, no existe un sistema de valoración clínica validado para la cuantificación de los signos clínicos asociados con CH. Objetivos: (i) determinar el mejor valor de corte de tres sistemas de puntuación, (ii) probar la precisión de cada sistema en comparación con el diagnóstico clínico de un veterinario experimentado y (iii) evaluar la equivalencia entre los sistemas. Animales: caballos islandeses (n = 20); ocho con CH y 12 no afectados, de un grupo de caballos de investigación que no recibian tratamientos para la dermatitis alérgica. Métodos y materiales: los valores de las lesiones se registraron cada dos semanas desde abril hasta septiembre con tres sistemas de calificación clínica (A, B y C) por un solo observador inicialmente desconocedor del estado de CH. Se utilizaron análisis de regresión logística separados para cada punto de tiempo para determinar los valores de corte apropiados para la clasificación de CH. Se calcularon el valor rho de Spearman y la kappa de Cohen para analizar la correlación de valores y la equivalencia en la categorización de CH entre sistemas, respectivamente. Resultados: se determinó que los mejores valores de corte de alergia para los sistemas A, B y C eran tres, ocho y 12, respectivamente. Para todos los sistemas, las áreas medianas bajo la curva (> 0, 85) fueron excelentes y la capacidad discriminatoria para clasificar correctamente el estado de CH fue elevada. Se determinó una excelente correlación entre los valores de cada sistema (rho de Spearman> 0, 96) y una excelente equivalencia entre sistemas para la categorización de CH (kappa ≥ 0, 73) en los puntos de tiempo valorados. Conclusión e importancia clínica: los resultados respaldan el uso de estos sistemas de puntuación como bases para la futura estandarización de un sistema de valoración clínica de la CH. Zusammenfassung: Hintergrund: Die Culicoides Hypersensibilität (CH), eine höchst juckende und saisonale allergische Dermatitis, ist eine häufige allergische Erkrankung, die Pferde weltweit betrifft. Zurzeit gibt es kein validiertes Bewertungssystem für die Quantifizierung einer klinischen Erkrankung, die mit CH zusammenhängt. Ziele: (i) Bestimmung des besten Cut‐Off Punktes bei drei Bewertungssystemen, (ii) Untersuchung der Genauigkeit eines jeden Systems im Vergleich zur klinischen Diagnose eines erfahrenen Tierarztes und (iii) Erfassung der Übereinstimmung zwischen den Systemen. Tiere: Islandpferde (n = 20); acht mit CH und 12 nicht betroffene Tiere aus einer Versuchsherde, die keine Behandlungen für allergische Dermatitis erhielten. Methoden und Materialien: Die Grade der Hautveränderungen wurden zweimal wöchentlich von April bis September mit drei klinischen Bewertungssystemen (A, B und C) durch einen einzigen, anfangs dem CH Status gegenüber geblindeten Untersucher, festgehalten. Eine separate logistische Regressionsanalyse wurde für jeden Zeitpunkt verwendet, um entsprechende Cut‐off Punkte für eine CH Klassifizierung zu bestimmen. Spearman´s RHO und Cohen´s Kappa wurden kalkuliert, um die Korrelation der Werte bzw. die Übereinstimmung der CH Kategorisierung zwischen den Systemen zu bestimmen. Ergebnisse: Die besten allergischen Cut‐Off Werte für die Systeme A, B bzw. C wurden bei drei, acht bzw. 12 festgelegt. Für alle Systeme waren die Medianflächen unter der Kurve (>0, 85) exzellent und die charakterisierende Fähigkeit, um CH Status korrekt zu klassifizieren, war stark. Es wurde bei allen Bewertungspunkten eine exzellente Korrelation zwischen den Werten für jedes System (Spearman´s RHO > 0, 96) und eine exzellente Übereinstimmung zwischen den Systemen für eine CH Kategorisierung (kappa ≥ 0, 73) festgestellt. Schlussfolgerungen und klinische Bedeutung: Die Ergebnisse unterstützen die Verwendung dieser Bewertungssysteme als Vorlagen für eine zukünftige Standardisierung eines klinischen Bewertungssystems für CH. 要約: 背景: 激しい掻痒性および季節性アレルギー性皮膚炎である Culicoides hypersensitivity (CH)は、世界中の馬に罹患する一般的なアレルギー性疾患である。現在、CHに関連した臨床徴候の定量化に対する有効な臨床採点システムはない。 目的: 本研究の目的は、(i)3つのスコアリングシステムの最良のカットオフポイントを決定すること、(ii)経験豊富な獣医師の臨床診断と比較したときの各システムの精度を調査すること、および(iii)システム間の一致を評価すること、である。 被験動物: アイスランドの馬(n = 20):アレルギー性皮膚炎の治療を受けていない研究群からCHに罹患した馬12頭および罹患していない8頭。 材料と方法: 病変スコアは4月から9月まで隔週で3つの臨床スコアリングシステム(A、BおよびC)を用いて一人の観察者により最初はCH状態を盲検化して観察された。各時点について別々のロジスティック回帰分析を用いて、CH分類の適切なカットオフを決定した。スピアマンのρとコーエンのκを、それぞれシステム間のスコアの相関とCH分類の一致を分析するために計算した。 結果: システムA、BおよびCの最良のアレルギーカットオフスコアを、それぞれ3、8および12と決定した。各系について、曲線下面積の中央値(> 0.85)は優れており、CH状態を正しく分類する識別能力は強かった。各システムのスコア間の優れた相関関係(Spearmanのρ> 0.96)とCH分類の優れたシステム間一致(kappa≥0.73)がスコアリング時点で見つかった。 結論および臨床的重要性: 結果は、CH臨床スコアリングシステムの将来の標準化のためのテンプレートとしてこれらのスコアリングシステムの使用を支持している。 摘要: 背景: 库蠓过敏(CH)是一种严重瘙痒、季节性和过敏性的皮炎, 是全世界的马均易感的常见过敏性疾病。目前, 尚无有效的临床评分系统来量化CH的临床病征。 目的: (i)确定三个评分系统的最佳分界点;(ii)与经验丰富的兽医作出的临床诊断相比较, 测试每个系统的准确性;(iii)评估系统之间的一致性。 动物: 未接受过敏性皮炎治疗的冰岛马(n = 20); 其中8匹患有CH, 12匹未患病。 方法和材料: 从4月到9月, 由最初对CH状态不知情的独立观察者以三种临床评分系统(A, B和C)记录病变评分, 每两周记录一次。对每个时间点分别进行逻辑回归分析, 以确定CH分类的适当分界点。分别用斯皮尔曼等级相关系数和科恩 kappa系数计算分析系统之间的得分相关性和CH分类的一致性。 结果: 系统A、B和C的最佳过敏分界值分别为3、8和12。 对于每个系统, 曲线下的中位数区域(> 0.85)均良好, 对CH状态分类的辨别能力很强。 在评分时间点内发现, 每个系统的得分(斯皮尔曼等级相关系数> 0.96)显著相关, CH分类的系统间一致性(kappa≥0.73)显著相关。 结论和临床意义: 结果支持使用这些评分系统未来作为标准化CH临床评分系统的模板。 Resumo: Contexto: A hipersensibilidade por Culicoides (CH), uma dermatite alérgica sazonal intensamente pruriginosa, é uma doença alérgica comum que afeta cavalos pelo mundo. Atualmente, não há um sistema de escore clínico validado para a quantificação dos sinais clínicos associados à CH. Objetivos: (i) determinar o melhor ponto de corte de três sistemas de escore, (ii) testar a acurácia de cada sistema comparado ao diagnóstico clínico de um veterinário experiente e (iii) avaliar a concordância entre os sistemas. Animais: Cavalos islandeses (n = 20); oito com CH e 12 não afetados, de um rebanho experimental, que não estavam recebendo nenhum tratamento para dermatite alérgica. Métodos e materiais: Os escores de lesão foram registrados a cada duas semanas de abril a setembro com três sistemas de escore clínico (A, B e C) por um único observador inicialmente cego ao status de CH. Análises de regressão logística separadas para cada tempo experimental foram utilizadas para determinar os pontos de corte apropriados para a classificação de CH. O rho de Spearman e o Kappa de Cohen foram calculados para analisar a correlação dos escores e a concordância da categorização de CH entre os sistemas, respectivamente. Resultados: Os melhores escores alérgicos para os sistemas A, B e C foram três, oito e 12, respectivamente. Para cada sistema a mediana das áreas sob a curva (>0, 85) foi excelente e a habilidade discriminatória de classificação correta de CH foi alta. Observou‐se excelente correlação entre os escores para cada sistema (Rho de Spearman > 0, 96) e excelente concordância entre sistemas para categorização de CH (kappa ≥ 0, 73) ao longo dos tempos experimentais. Conclusão e importância clínica: Os resultados corroboram com o uso dos três sistemas de escore como modelos para uma futura padronização de um sistema de escore para CH.